Teen Digital Language and Identity Formation: A Corpus-Driven Multimodal Linguistic Landscape Analysis on Social Media Platforms - Isnawita Mokodompit; Nonny Basalama; Sartin T. Miolo; Muziatun (WISE Pendidikan Indonesia, 2026)
The intensification of social media has significantly altered the linguistic landscape among teenagers, influencing identity formation and communication practices. This research investigates how social media platforms, such as Instagram, TikTok, and WhatsApp, shape teens language by studying the forms, types, components, and functions of linguistic landscapes in virtual spaces. Qualitative method with ethnography design was used in this study and utilized corpus-driven data collection techniques. This research conduct in MAN 1 Kota Gorontalo to analyzes language use among middle level students, aged 17-18. It investigates the emergence of digital language as new linguistic forms consist of; slang, abbreviations, emojis/stickers, and memes, until their effect in constructing digital identities. Essentially, this study offers theoretical novelty by concerning the new concept of linguistic landscape (LL) in virtual public spaces, showing how the digital platform creates various kind of linguistic form. The findings reveal that teen language in social media is highly dynamic, reflecting both the social and cultural aspects of identity. Besides, the study also identifies the social conflicts that caused from language use, such as generational gaps and misunderstandings between teens and authority figures, highlighting the ethical challenges in digital communication. The study completes by highlighting the need for academical interventions to handle the ethical problem caused by engage teen language in the digital era and suggests strategies for fostering responsible digital communication.